PELATIHAN GURU DALAM PENGGUNAAN PLATFORM PEMBELAJARAN DARING DI SMP SANTO FRANSISKUS ASISI PONTIANAK - Role, Metoddyus Tri Brata; Kurniawan, Apri; Zulkarnain, Rezkie (Amare, 2024)
At the beginning of 2020, the world faced the significant impact of the coronavirus (COVID-19) pandemic, including on the education sector in Indonesia. The shift to online learning became a crucial policy in response to the pandemic emergency. Training on the use of online learning platforms, particularly Google Classroom, at SMP Fransiskus Asisi Pontianak Utara was the focus of this community service. The aim was to enhance teachers' competence in managing online learning and assist parents in supporting their children's learning at home. The method involved direct training by competent instructors, accompanied by question-and-answer sessions and in-depth material exploration. The results showed a significant improvement in teachers' understanding and skills in using Google Classroom, as well as a positive effect on student interaction and learning quality. Recommendations for the future include continuing similar training programs with sustained support and mentoring. The outcomes of this community service have important implications for enhancing the quality of online learning during the pandemic and beyond, as well as preparing teachers to face the challenges of hybrid learning. Therefore, this service has high relevance in the context of learning in the current digital era.